Topic: blogspot for modeling as a strategy to improve english reading fluency in students of ninth grade at ebg josé pedro varela, La Libertad, province of Santa Elena. 2015 – 2016. - Campoverde Guerrero, Arens Dayan (2015)
Today’s society integrates the use of information and communication technologies (ICTS) and it is precisely in education where technological strategies should be implemented. This will allow students to consolidate the acquired knowledge, question the knowledge, and look for new knowledge always supervised by the teachers in their role of guidance of the process. Modeling strategy is used to help students to read fluently by repeating what the teacher is reading aloud. In this research, teachers do not play the role mentioned before (reading aloud), but the BlogSpot and the tools will do it instead. The present research shows the improvement of the English reading fluency of ninth grade students EBG at José Pedro Varela through the implementation of a BlogSpot. As the fundamental base of the research, blogger has been used as well as other important web tools which are helpful for the improvement of the reading skill.